Analisis Sarana, Prasarana , dan Utilitas Umum pada Dinas Perumahan dan Kawasan Permukiman serta Pertanahan Kabupaten Deli Serdang - Muammar Al Hafiz; Muhammad Ikhsan Harahap M.E.I (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The implementation of the internship program which took place on 16 January-16 February 2022 at the housing and residential areas and land services of Deli Serdang district was packaged with the concept of 1) problem solving by students taking part in the internship program after carrying out the problem identification stage and 2) implementing a series of training activities by the housing and residential areas and defense services for students taking part in the internship program. The methods used in this internship program are summarized in three stages, namely 1) preparation stage, 2) implementation stage, and 3) evaluation stage which includes making a final report. This skills internship program is effective as a place for students to practice the knowledge they have absorbed in lectures directly in the workplace, increase students' insight and experience, improve students' skills and competencies in certain areas of expertise through various training, and equip students with skills that can be utilized. after graduating from college. Through the implementation of this skills internship program, students are not only required to do work practice at partner companies where they do internships. Students are also trained to be able to work and collaborate in teams and be effective in improving skills and competencies in certain areas of expertise.